دراسة الفروق في مستوى المهارات الحركية الأساسية بين تلاميذ المدارس الإبتدائية لولاية بسكرة - beggar nacer (sports creativity, 2025)
The study, entitled "Study the differences in the level of basic motor skills among primary schools’ pupils in the wilaya of Biskra" aims to identify the differences in the level of basic motor skills of primary schools pupils, according to sex and physical practice variable (pupilspracticing and non-practitioners of physical and Sport education). We have adopted the descriptive analytical approach which is appropriate for such field study, and our study community consists of all primary school pupils of the wilaya of Biskra, who are limited to (10 years) and who represent the fifth primary year, the study sample included 127 pupils, based on our selection on a simple random sample, and in order to test the hypotheses of the study was used (TGMD) test, which includes eight tests measuring basic motor skills, which was distributed to : * Transitional skills: (running, partridge, jumping, jumping In front of fortitude( * Control and control skills: (throwing the ball, standing, kicking, throwing the ball above the shoulder level).